2005
DOI: 10.7589/0090-3558-41.4.758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Remotely Delivered Leuprolide Acetate as a Contraceptive Agent in Female Elk (Cervus Elaphus Nelsoni)

Abstract: Practical application of fertility control technology in free-ranging wild ungulates often requires remote delivery of the contraceptive agent. The objective of this investigation was to evaluate the potential of remote delivery of leuprolide acetate for suppressing fertility in female elk (Cervus elaphus nelsoni). Fifteen captive adult female elk were randomly allocated to one of three experimental groups. Six elk were injected intramuscularly with a dart containing leuprolide, and the remaining nine elk rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…All treated elk regained normal reproductive function and conceived the next year. These findings are consistent with previous studies of captive elk (Baker et al 2002(Baker et al , 2005, and they provide unambiguous evidence that leuprolide formulation can be a highly effective, short-term contraceptive agent in this species. Moreover, these results concur with those from previous studies in which long-acting GnRH agonist formulations effectively controlled reproduction in other mammalian species (Trigg et al 2001, D'Occhio et al 2002, Baker et al 2004, Herbert et al 2005, Herbert and Cooper 2006.…”
Section: Discussionsupporting
confidence: 92%
“…All treated elk regained normal reproductive function and conceived the next year. These findings are consistent with previous studies of captive elk (Baker et al 2002(Baker et al , 2005, and they provide unambiguous evidence that leuprolide formulation can be a highly effective, short-term contraceptive agent in this species. Moreover, these results concur with those from previous studies in which long-acting GnRH agonist formulations effectively controlled reproduction in other mammalian species (Trigg et al 2001, D'Occhio et al 2002, Baker et al 2004, Herbert et al 2005, Herbert and Cooper 2006.…”
Section: Discussionsupporting
confidence: 92%
“…In this subspecies (Baker et al 2002(Baker et al , 2005Conner et al 2007) leuprolide-treated animals did not become pregnant during the breeding season following treatment. In accord with the present results for males, Baker et al (2002Baker et al ( , 2005) also reported suppression of plasma LH concentration in the females. Also, in concert with results of the studies in females, our observations showed little effect of leuprolide on behaviour of the males.…”
Section: Discussionmentioning
confidence: 95%
“…Recent advances in development of biodegradable implants containing GnRH agonists have led to sustained-release delivery systems that have provided long-term contraceptive effects in heifers and cows following use of implants containing deslorelin (D'Occhio et al 2002). In deer, biodegradable implants containing leuprolide, another GnRH agonist, have successfully generated reversible long-term contraception in wapiti (Cervus elaphus) females (Baker et al 2002(Baker et al , 2005Conner et al 2007). The present study was conducted to determine whether such implants containing leuprolide would mitigate negative effects of the rut on liveweight and body condition in red deer males -another subspecies of Cervus elaphus.…”
Section: Introductionmentioning
confidence: 99%
“…We also studied the effect of this treatment on reproductive behaviors both during and after the captive breeding season (October-November). Finally, we tested whether this high viscosity gel could be effectively delivered from a remote dart delivery system (Baker et al 2005). Interestingly, we found elk to be quite sensitive to GnRH agonist suppression.…”
Section: Gonadotropin Releasing Hormone Agonistmentioning
confidence: 99%